A study to find out the reasons why car dealers sales declined / Sany Abdillah Hj. Ahmad - Abdillah HJ. Ahmad, Sany (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2006)
This project paper was written as part of the requirements for the Degree Course Bachelor of Business Administrations (Hons) majoring in Marketing Course. The main objectives of this project are to provide and in-depth analysis on the reasons why the car dealers' sales declined and as well as to determine the level of acceptance of Mayfin Centre based on feedback given by the car dealers (the main respondents) in Kota Kinabalu through this survey. A total of 30 questionnaires were distributed pertaining to the study, out of which 20 were completed and returned. The questionnaires were analyzed to determine the responses from the respondents. Interviews with the sales representatives and company managing directors and owners were also made in the course of finalizing this analysis. Nevertheless in the course of writing this paper, I have done my level best to be consistence with the original objectives of the study and also provided my own opinions and views based on feedings of the research, reference book, newspaper as well as internet sources. The study is basically about the reasons why the car dealers' sales declined and the level of acceptance/satisfaction towards Mayfin Centre services. The main issues in this research are to find out factors contribute to the declining sales of the car dealers' and the popularity of Mayfin Centre.